Optimized electrical control of a Si/SiGe spin qubit in the presence of an induced frequency shift. (December 2018) - Takeda, K.; Yoneda, J.; Otsuka, T.; Nakajima, T.; Delbecq, M.; Allison, G.; Hoshi, Y.; Usami, N.; Itoh, K.; Oda, S.; Kodera, T.; Tarucha, S.
Abstract Electron spins confined in quantum dots are an attractive system to realize high-fidelity qubits owing to their long coherence time. With the prolonged spin coherence time, however, the control fidelity can be limited by systematic errors rather than decoherence, making characterization and suppression of their influence crucial for further improvement. Here we report that the control fidelity of Si/SiGe spin qubits can be limited by the microwave-induced frequency shift of electric dipole spin resonance and it can be improved by optimization of control pulses. As we increase the control microwave amplitude, we observe a shift of the qubit resonance frequency, in addition to the increasing Rabi frequency. We reveal that this limits control fidelity with a conventional amplitude-modulated microwave pulse below 99.8%. In order to achieve a gate fidelity >99.9%, we introduce a quadrature control method, and validate this approach experimentally by randomized benchmarking. Our finding facilitates realization of an ultra-high-fidelity qubit with electron spins in quantum dots. Quantum-dot spin qubits: Correcting systematic errors Systematic errors are discovered in semiconductor spin qubits but so are ways to correct for them. One of the key challenges in building a quantum computer is the development of a suitable platform to act as the fundamental building block - the quantum bit (qubit). Electrons spins that are confined in quantum dots of conventional semiconductors like silicon are an attractive candidate as the materials and processing technology are well-developed and scalable, and the quantum states have long lifetimes. However, an international research team led by Kenta Takeda from the RIKEN Center for Emergent Matter Science have now identified systematic errors that emerge when trying to manipulate such qubits. Although the exact origin of these errors is not clear, the team present an approach for mitigating them.